2018
DOI: 10.1016/j.neurobiolaging.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association identifies a novel locus for delirium risk

Abstract: We aimed to identify common genetic variations associated with delirium through genome-wide association testing in a hospital biobank. We applied a published electronic health record based definition of delirium to identify cases of delirium, and control individuals with no history of delirium, from a biobank spanning two Boston academic medical centers. Among 6,035 individuals of Northern European ancestry, including 421 with a history of delirium, we used logistic regression to examine genome-wide associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Furthermore, neuroimaging studies indicate that the risk of delirium might be higher in individuals with greater cerebral atrophy and/or greater white matter disease 46,47 . Genetic studies have not identified consistent candidate genes associated with delirium risk but these studies are few and underpowered 48,49 .…”
Section: Prevalence Estimatesmentioning
confidence: 99%
“…Furthermore, neuroimaging studies indicate that the risk of delirium might be higher in individuals with greater cerebral atrophy and/or greater white matter disease 46,47 . Genetic studies have not identified consistent candidate genes associated with delirium risk but these studies are few and underpowered 48,49 .…”
Section: Prevalence Estimatesmentioning
confidence: 99%
“…In the research field of delirium, there are so far only two studies that have conducted a GWAS [ 13 , 14 ], whereas in the field of postoperative neurocognitive disorders (which includes POCD), to the best of our knowledge, no GWAS have yet been published. With regard to POD, a study by McCoy et al was able to identify a single locus on Chr2 associated with the development of delirium in hospitalized patients [ 13 ]. It contained multiple genes, none of these, however, was part of the cholinergic system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors responsible for the disturbance of cholinergic neurotransmission are not sufficiently understood. Genome-wide association studies (GWAS) have so far been unable to identify a link between the cholinergic system and the development of POD and POCD [ 13 , 14 ], although numerous polymorphisms are located in the cholinergic system [ 15 ] and a connection to inflammation has already been established [ 16 ]. To confirm the evidence so far of the two previous GWAS, we first performed a GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…Delirium is considered the most common complication afflicting hospitalized elderly patients, and is associated with poor outcomes, including increased hospital stays and high morbidity and mortality rates [ 4 ]. The pathophysiological underpinnings of delirium are complex, and multiple contributing mechanisms have been identified [ 5 , 6 ]. These include direct and indirect effects of inflammatory, neuroendocrine, and gross anatomic or neurodegenerative mechanisms [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, candidate gene association studies on delirium have shown that apolipoprotein E [ 8 ], catechol-O-methyltransferase (COMT) [ 9 ], and dopamine-signaling genes such as dopamine receptor 2 [ 10 ] are related to the risk of delirium. Interleukin-related genes and the sodium/hydrogen exchanger gene were also identified as risk factors for delirium by a delirium-focused genome-wide association study (GWAS) [ 6 ]. Although these factors are thought to be important for the pathogenesis of delirium, it is largely unclear how the genes associated with delirium contribute and which of them play key roles.…”
Section: Introductionmentioning
confidence: 99%